RIFLE serum creatinine and urine output criteria combined is superior to RIFLE serum creatinine criterion alone in predicting Acute Kidney Injury (AKI) in critically ill patients: A prospective observational study (Bangladesh Critical Care Journal, 2020)
Background: Approximately 7% of all hospitalized patients and 20% of acutely ill patients develop signs of AKI. AKI incidence is very high worldwide among intensive care unit patients. Previously long known term, acute renal failure (ARF) is largely replaced by acute kidney injury (AKI), reflecting the recognition that smaller decrements in kidney function that do not result in overt organ failure are of substantial clinical relevance and are associated with increased morbidity and mortality.Objectives: We designed this study to diagnose even mild renal dysfunction earlier than usual time frame with the combined effect of both serum creatinine and urine output criteria, when compared with serum creatinine criterion alone. To establish this objective we used RIFLE serum creatinine and urine output (UO) criteria combined (Scr+UO) and compared with RIFLE serum creatinine (Scr) alone to diagnose AKI early (in days).Design: Prospective observational cohort study. Duration of the study was one year (01 year), from January 2014 to December 2014Method: All adult patients admitted into department of critical care medicine, BIRDEM General Hospital, DHAKA who received treatment for 48 hours and fulfilled the inclusion and exclusion criteria was included in the study. Representative serum creatinine value was obtained either from the day of admission in hospital, day of admission into or transfer to ICU or any document within last six months. The lesser of pre-ICU admission serum creatinine (SCr) and ICU admission SCr would serve as baseline renal function. Weight in kilogram, representative serum urea/BUN, co-morbidities and reason for ICU admission were incorporated in it. Patient’s daily data entry of renal replacement therapy, daily creatinine value, urinary output over 6 hours, 12 hours, and 24 hours, episode of anuria over 12 hours, if present were documented. Data collected on renal replacement therapy at the time of discharge, if any and outcome in terms of loss and ESRD status were collected. APACHE II data and SAPS II data were calculated and analyzed.Result: Total 236 adult patients were enrolled in the study to assess their renal function status using RIFLE (Risk, Injury, Failure, Loss, End Stage Renal Disease). Serum creatinine was estimated daily for seven days. Those patients who fulfilled the creatinine criteria for RIFLE were categorized into RIFLE serum creatinine (Scr) group. Those patients who met both the criteria for urine output and serum creatinine according to RIFLE was designated as RIFLE serum creatinine and urine output criteria Combined (Scr+ UO) group. In our study, mean of number of days needed for diagnosis of AKI using RIFLE creatinine (Scr) was 3.25 (±1.24) and using RIFLE combined (Scr+uo) criteria was 2.84(±1.03).Conclusion: The present study concludes that RIFLE serum creatinine criterion (Scr) alone delays the diagnosis of AKI in comparison to RIFLE serum creatinine and urine output criteria combined (Scr+UO). AKI should be graded using both the criteria of RIFLE serum creatinine and urine output criteria combined (Scr+UO). Urine output should not be underestimated in AKI diagnosis in ICU patients.Bangladesh Crit Care J March 2020; 8(1): 17-23